METHODS OF BIOMECHANICAL ANALYSIS IN SPORTS (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
The evaluation of strategies and approaches is what biomechanical analysis encompasses in the world of sports. The use of numerical values is not permitted in qualitative methods when describing quality. The quantitative analytical method consisted of the collection of data, the measurement of that data, and the interpretation of that data using numerical variables. The recall accuracy rate of athletes and coaches respectively is a pitiful thirty percent. The remaining seventy percent is helped along by performance analysis, which assists in providing accurate data on performance. The key focuses of this systematic review article are on biomechanics and the many approaches to biomechanical performance analysis that are utilised in the sporting world. Athletes Athletes and coaches frequently seek the advice of biomechanists, who are experts in analysing and dissecting athletic technique, in order to enhance performance and reduce the risk of injury. When it comes to approaching athletic skills in order to achieve optimal performance, the knowledge that sport biomechanics can convey can be of tremendous use to both athletes and coaches. Consequently, all of the organisations that are involved in the expansion of the sport and the improvement of the athletic performance of coaching staff, such as clubs, institutions, academies, managers, and players, are obligated to participate.